Epidemiology of HPV Infection and HPV-Related Cancers in Kazakhstan: a Review - Aimagambetova, Gulzhanat; Azizan, Azliyati (About Asian Pacific Journal of Cancer Prevention, 2018)
Background: Cancer is one of the most prevalent causes of mortality worldwide. In the cervix it is considered to be caused by different high-risk human papillomavirus (HPV) types. Although many studies have already been conducted worldwide on the epidemiology of HPV infection and their oncogenic properties, limited data are available on HPV prevalence, incidence and genotype specific dissemination in Kazakhstan. Methods: To review the distribution of HPV infection, electronic databases (e.g. PubMed, Web of Science and Google Scholar) were searched for peer reviewed articles in English. The study was performed during June-July 2017 with a review of 39 relevant articles, published up to July 31, 2017. The following inclusion criteria were applied: general population data, cytology results available, and use of polymerase chain reaction (PCR) and/or Hybrid Capture® 2, Digene Corp., USA for HPV detection. Results: As reported in limited studies, the prevalence of HPV infection in Kazakhstan ranges from 43.8% to 55.8%. However, the scenario with regard to epidemiology of HPV related cancers in Kazakhstan is not very clear. One study reported a decline of laryngeal cancer observed during the recent years, whereas cervical cancer incidence has increased to about 3000 new cervical cancer cases, and about 1,000 cervical cancer deaths each year. Conclusion: The high incidence of cervical cancer with a significant mortality rate in Kazakhstan is evidence of HPV infection abundance despite an absence of HPV screening and low public awareness of the problem. Having a well-informed understanding of the role of HPV infection could enhance the public’s acceptance of screening and intervention programs to reduce morbidity and mortality in the country due to HPV infection. Thus, the purpose of this review article is to summarize the existing data, identifying directions for future research on HPV epidemiology and HPV-related diseases in Kazakhstan.
Keywords: Human papillomavirus (HPV); cervical cancer; HPV epidemiology; related cancers; HPV vaccination